Experimental dryer design for agricultural products - GONELI,ANDRÉ L. D. (2016)
ABSTRACT This study consisted of designing and building an experimental dryer that allows working with different temperatures and velocities of the air, aiming to perform studies on thin- and thick-layer drying of agricultural products. The project was divided into three stages: heat source designing, dryer geometric parameters, and fan selection to meet operational demand. Heating was made by a set of six electrical resistances totaling 12 kW and the drying bed in thin layer was composed of two trays with diameter of 0.20 m. Operational demands were met using a centrifugal fan with a power rating of 735.5 W. The used methodology was able to size the experimental dryers for thin- and thick-layer drying working at distinct temperatures and air velocities.